Financial inclusion and tax revenue - Gamze Oz-Yalaman (Central Bank Review (CBR), 2019)
Financial inclusion might bring huge amounts of income into the global economy, which creates different opportunities and challenges for countries. As people become more financially included and their incomes grow over time, this might in turn increase their tax contributions to the government. Thus, this paper seeks an answer to the primary question of whether the changes in tax revenue is associated with the change in financial inclusion for countries around the world by using an extensive dataset of 137 countries over the years between 2011 and 2017. For this, the paper uses the Global Findex database and panel data methodology. The empirical findings show that there is a significant and positive relationship between financial inclusion and tax revenues and it is one of determinants of tax revenues. The results are robust in terms of different sources of taxation such as corporate tax revenue, income tax revenue and direct tax revenue. Policy-makers around the world could take advantage of this significant opportunity in order to raise tax revenues by considering ways of increasing financial inclusion.
Keywords: G21; H24; O16; 330; Financial inclusion; Tax revenue; Panel data; Global findex